Occurrence of Giardia and Cryptosporidium (oo)cysts in the river water of two recreational areas in Selangor, Malaysia - Azman, Jali; Ithoi, Init; Wan Sulaiman, Wan Yusoff (Malaysian Society of Parasitology and Tropical Medicine, 2009)
This study is the first report on the occurrence of Giardia and Cryptosporidium (oo)cysts in recreational rivers water from Malaysia. It was carried out in water samples at two rivers, 'Sungai Congkak' and 'Sungai Batu', located in Selangor State. The occurrence of both Giardia lamblia and Cryptosporidium parvum (oo)cysts was higher in Sungai Congkak (50 or 15/30 and 10 or 3/30 respectively) than Sungai Batu (16 or 5/30 and 3.3 or 1/30 respectively). The mean density of cysts/L was 0.72 in Sungai Congkak and 0.023 in Sungai Batu, and that of oocysts/L was 0.023 in Sungai Congkak and 0.0033 in Sungai Batu, showing that the occurrence of Giardia was higher and more frequent than Cryptosporidium in both rivers. Sungai Congkak also showed higher faecal coliforms count (ranging from 0.48x10(3) to 73x10(3) CFU/100 mL) than Sungai Batu (0.41x10(3) to 16x10(3) CFU/100 mL). On the other hand, the Giardia and Cryptosporidium (oo)cysts and faecal coliforms were more concentrated at the downstream station, followed by midstream and upstream stations which might be due to human factors where settlements and recreation areas were located around and between midstream and downstream stations. The (oo)cysts and faecal coliforms also increased during public holidays due to the significantly higher number of visitors (bathers) compared with the week days. All the parameters (physical, faecal coliforms and rainfall) did not show consistent significant correlation (based on r values of Pearson correlation analysis) with both protozoa, therefore these parameters are not suitable as indicator for the presence of Giardia and Cryptosporidium (oo)cysts in both rivers.